2019
DOI: 10.1016/j.jad.2019.03.029
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of dispositional compassion for others with depressive symptoms over a 15-year prospective follow-up

Abstract: Background: The aim of this study was to investigate (i) the direction of the relationships between dispositional compassion for others and depressive symptoms over a 15-year follow-up in adulthood and (ii) the longitudinal associations of dispositional compassion with total depressive symptoms and various depressive subsymptoms (i.e. negative attitude, performance difficulties, and somatic complaints) from early adulthood to middle age. Methods: The participants (N=1676) came from the prospective Young Finns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 73 publications
(95 reference statements)
2
7
0
1
Order By: Relevance
“…On the one hand, patients with chronic depression also reported significantly reduced compassion to close others. This result is consistent with findings of reduced dispositional compassion (20) and reduced empathy -as an integral part of compassion -in depression (12). On the other hand, and contrary to our expectations, compassion was not impaired toward strangers or other humans in general.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the one hand, patients with chronic depression also reported significantly reduced compassion to close others. This result is consistent with findings of reduced dispositional compassion (20) and reduced empathy -as an integral part of compassion -in depression (12). On the other hand, and contrary to our expectations, compassion was not impaired toward strangers or other humans in general.…”
Section: Discussionsupporting
confidence: 89%
“…Although previous research demonstrated that selfcompassion is reduced in depression, research on the role of compassion toward others in depression is sparse. A recent longitudinal study on the relationship between dispositional compassion and depressive symptoms found that among adolescents and young adults, high levels of dispositional compassion predicted lower depression, whereas conversely, depression was not likely to influence compassion (20). However, depressive symptoms were only mild and non-clinical in the sample studied.…”
Section: Introductionmentioning
confidence: 76%
“…Confirmatory factor analysis showed that construct validity of the compassion scale was excellent [30]. Additionally, the internal consistency of the scale was found to be high (Cronbach's α = .86-.88 in 1997-2012).…”
Section: Methodsmentioning
confidence: 87%
“…It is a separate concept from self‐compassion (i.e., compassionate attitude toward the suffering of the self; Barnard & Curry, 2011) and compassion from others (i.e., compassionate expressions received from others for the suffering of the self; Gilbert, 2019). Compassion for others predicts lower depression (Saarinen, Keltikangas‐Järvinen, Cloninger, et al., 2019) and, previously, intervention studies have demonstrated that compassion‐training interventions are linked to decreased concentrations of CRP and decreased responses of IL‐6, cortisol, and adrenocorticotropic hormone (ACTH) to psychosocial stress (Abelson et al., 2014; Pace et al., 2009). Finally, compassionate states correlate with the activity of hypothalamus (Immordino‐Yang et al., 2009) that is involved in the regulation of inflammatory responses (Black, 2002).…”
Section: Introductionmentioning
confidence: 99%